Regulatory T Cell in Stroke: A New Paradigm for Immune Regulation - Sheng Chen; Haijian Wu; Damon Klebe; Yuan Hong; Jianmin Zhang; Jiping Tang (Clinical and Developmental Immunology)
Stroke is a common, debilitating trauma that has an incompletely elucidated pathophysiology and lacks an effective therapy. FoxP3+CD25+CD4+ regulatory T cells (Tregs) suppress a variety of normal physiological and pathological immune responses via several pathways, such as inhibitory cytokine secretion, direct cytolysis induction, and antigen-presenting cell functional modulation. FoxP3+CD25+CD4+ Tregs are involved in a variety of central nervous system diseases and injuries, including axonal injury, neurodegenerative diseases, and stroke. Specifically, FoxP3+CD25+CD4+ Tregs exert neuroprotective effects in acute experimental stroke models. These beneficial effects, however, are difficult to elucidate. In this review, we summarized evidence of FoxP3+CD25+CD4+ Tregs as potentially important immunomodulators in stroke pathogenesis and highlight further investigations for possible immunotherapeutic strategies by modulating the quantity and/or functional effects of FoxP3+CD25+CD4+ Tregs in stroke patients.